Práticas integrativas e complementares no sistema público de saúde brasileiro: análise de uma rede sociotécnica - Melo, Aislan Vieira de (2023)
Non-conventional therapies are officially offered by Brazilian public health service since 1980s and have been widely offered after the institutionalization of National Policy for Integrative and Complementary Practices in Unified Health System (PNPIC – Portuguese anacronym) in 2006. Many studies have analyzed this public policy from the implementation point view which emphasize the comparison between the institutionalized document, considered “the policy”, and the actions carried out, aiming find and point out flaws, gaps, or success in the execution of the “policy”. This thesis uses actor-network theory and assemblage approach as theoretical-methodological tools to analyze the PNPIC and to avoid the comparative perspective. While the actor-network theory has been a path little explored of analyzes in research on the subject, the use of the assemblage approach is a novelty yet. The choice for this analytical path entails to take some assumptions. The first one is to assume symmetric ethnography as methodological tool and, consequently, to assume that policy is constituted by actors of various materialities (such as human beings, documents, objects, institutions) that engaged with each other through their actions making emerge realities. Following these assumptions is to assume that policy alone does not able to influence reality but must associate or to be associated with other actors to emerge and to be able to influence it. Still, the institutionalization document is perceived as one of possible versions of the policy through which it come to life in reality. This document comes to light as result of the silencing possible versions of the policy which proposed how it should be. In this scope, policy is configured as something in motion and that is being distributed across many spaces of society, insofar associate itself or it is associated with other actors. The thesis aim was to analyze how the PNPIC have been made by many actors across many contexts, that is to analyze the process that make it emerge in reality in version multiples. The results demonstrate that policy is being appropriated by various actors in these spaces and receiving new meanings, making emerge contextualized versions of the policy, such as legal device, political capital, academic and professional expertise, among others. At the same time, some these new meanings are understood as contestation processes that may or may not result in changes (version silencing) of the current policy document. Accordingly, the results demonstrate the fluidity and potentiality of the policy from the spaces where it is presents, some of which were addressed in this thesis, such as: as part of health actions and policies provided by Health Ministry; in the framework of specific policies for non-conventional therapies institutionalized by Brazilian states and capital of states; in the context of COVID-19 pandemic; in the framework of health work conseils that have been regulating non-conventional therapies as professional activities, before Brazilian government and including therapies that are not inserted in PNPIC; in the framework of discuss around scientific evidences this kind of therapies. Therefore, the results this study presents the PNPIC emphasizing its potential to contribute to the emerge of multiple and contextual realities.